География голубого континента - Богданов Даниил Васильевич (Научно-популярная серия, 1963)
Экземпляры: КХ (20121015) / Инвентарный номер: 0136374 / Цена: 0.13 / Сис.шифр: 551.49 / Авт.знак: Б 73 / ГРНТИ: 70 / ББК: 26